Human Mental Activities: An Integrative Study of Islamic and Scientific Perspectives and Their Implementation in Curriculum - Lalu Sudianto; Ahmad Sulhan; Maimun Maimun; Mira Mareta (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This research aims to analyze human mental activities through an integrative study of Islamic and scientific perspectives and to examine their implementation within curriculum development. The study employs a qualitative approach with the type of literature study (library research). Data were collected through documentation techniques from classical Islamic literature, contemporary scientific references, academic journals, books, and educational policy documents related to cognition, neuroscience, Islamic epistemology, and curriculum studies. The data were analyzed using descriptive-analytical, interpretative, and comparative approaches to identify the convergence between Islamic concepts and scientific theories concerning human mental activities. The findings reveal that human mental activities encompass interconnected cognitive, emotional, moral, and spiritual dimensions that cannot be adequately explained through a single epistemological framework. Scientific perspectives provide empirical explanations concerning neurobiological and cognitive mechanisms, whereas Islamic perspectives contribute ethical, spiritual, and transcendental orientations through concepts such as ‘aql, qalb, nafs, and ruh. The study further demonstrates that the integration of both perspectives may reconstruct curriculum paradigms toward holistic education emphasizing intellectual competence, emotional maturity, moral responsibility, and spiritual awareness. This research implies the necessity of developing integrative curriculum frameworks capable of harmonizing scientific inquiry with ethical-spiritual values to address contemporary educational and societal challenges. Keywords: Human Mental Activities; Integrative Curriculum; Islamic and Scientific Perspectives.